Competency Enhancement and Effective Communication as Drivers of Organizational Performance: An Application of the Work Competence Theory - Golda Agustha Sagrim; Vebby Anwar; Wa Ode Likewati; Munzir Munzir (Manajemen Bisnis, 2026)
This article explores the impacts of competency enhancement strategies and effective communication on organisational performance by applying the Theory of Work Competence. The research aims to analyse both the direct and indirect influence of improving work competence and effective communication in an organisational setting. A quantitative approach was employed, utilising questionnaires distributed to organisational employees, and data was analysed using multiple linear regression. The findings indicate that both competency enhancement strategies and effective communication have a significant positive effect on organisational performance, both individually and simultaneously. Employees who possess more competence and engage in effective communication demonstrate improved performance, contributing to the achievement of organisational goals. The study concludes that developing work competencies and fostering effective communication are key drivers of organisational success. It is recommended that organisations implement continuous training programmes and establish open communication channels to sustain and further enhance their performance. Future research should consider additional factors, such as leadership style and organisational culture, to provide a more comprehensive understanding of performance improvementss.